Preparedness in Long-Term Care: A Novel Approach to Address Gaps in Evacuation Tracking. (29th December 2016) - Prot, Emilie Y; Clements, Bruce
Abstract: With an aging population, the number of elderly individuals residing in long-term care (LTC) facilities will continue to grow and pose unique challenges to disaster preparedness and response. With this rapidly growing vulnerable population, it becomes imperative to identify enhanced and novel preparedness strategies and measures. LTC residents not only have complicated medical needs, including the timing of dispensing multiple medications, but frequently have cognitive and mobility deficits as well. In nearly every major disaster, elderly populations have suffered disproportionate morbidity and mortality. This is often due to elderly evacuees getting overlooked in the chaos of an initial response. Instituting measures to rapidly recognize this population in a crowd during an evacuation will reduce their risk. This commentary reviews the LTC facility evacuation challenges of the 2013 explosion of the West Fertilizer Company plant in West, Texas, and offers a novel solution of mandating the wearing of pink vests by all nursing home residents in case of an evacuation. The pink vests quickly alert disaster rescue and response workers of LTC residents with special needs. ( Disaster Med Public Health Preparedness . 2017;11:28–30)